Effects of river input flux on spatiotemporal patterns of total nitrogen and phosphorus in the Pearl River Estuary, China - Ke, Sheng; Cai, Zhimei; Zhang, Peng; Zhang, Junxiao; Zhang, Jibiao (Frontiers in Marine Science, 2023)
The increasing riverine nutrient sources have significantly affected the ecological environment of estuaries and coastal waters, resulting in deteriorating land-sea water quality and intensified eutrophication. However, the effects of river input flux on spatiotemporal patterns of total nitrogen (TN) and total phosphorus (TP) were poorly understood in the Pearl River Estuary (PRE). In this study, the spatiotemporal patterns of TN and TP concentrations and river input flux of PRE were studied based on the seasonal nutrients monitoring data obtained for the rivers and estuary in 2019. The results showed the spatiotemporal patterns of the TN and TP concentrations in the eight rivers of the PRE were different, and the annual average concentrations of TN and TP in the rivers entering the PRE were 207.18 ± 105.13 and 3.51 ± 1.70 μmol/L, respectively. The annual river TN and TP fluxes discharged into the PRE were 8.61 × 1010 and 1.55 × 109 mol/year, respectively. In addition, the significantly decreasing trends in of TN and TP concentrations from upper estuary to offshore seawater were observed in the PRE, which implied TN and TP showed conservative behaviour in all season and only the dry season, respectively. Moreover, the annual average concentrations of TN and TP in the estuary were 70.64 ± 10.10 and 1.67 ± 0.78 μmol/L, respectively. The annual average ratios of TN/TP for rivers, freshwater, mixed and seawater were 59.31 ± 5.98, 59.45 ± 3.75, 45.73 ± 21.27 and 330.94 ± 434.71 respectively, which were higher than the Redfield ratios. These results indicated that the water quality in most areas of the PRE is significantly polluted and that the TN and TP in seawater were significantly influenced by river inputs. Therefore, monitoring and management of unified TN and TP nutrient indicators discharge from rivers entering the sea can be strengthened in the PRE, and eutrophication mitigation strategy should be established and implemented across river-estuary-coast continuum systems in the Great Bay Area.